Sistem Monitoring Kolesterol Melalui Iris Mata dengan Metode Pengolahan Citra - Abdul Fadlil; Wahyu Sapto Aji; Arief Setyo Nugroho (Universitas Syiah Kuala, 2020)
Early detection to determine the presence or absence of cholesterol in the body is a necessity for everyone who wants to live healthy. Many diseases can be caused by the presence of cholesterol such as heart disease, stroke, nerve disorders, kidney problems, hypertension, and etc. Therefore, cholesterol detection must be done regularly. This study discusses about the cholesterol detection system through the iris eyes using image processing and monitoring progress in continously. Detection of cholesterol can be observed with Arcus Senilis or a gray ring in the iris eyes. Tests carried using 15 samples which cholesterol identifed. The process of image processing consists of image acquisition, sharpening, segmentation, convert grayscale and binary images. Cholesterol can be identify with difference between pixel values 0 (black) and pixel values 1 (white) in binary images. Research data will be stored in an Excel format database with adding some user data. From the test, results analysis carried the try and error threshold method using values of 80, 100, 150, and getting an accuracy of 87%, 73%, and 33%. Besides, monitoring cholesterol can be carried using a system interface and database with adding the required data and can display it on excel.